2020
DOI: 10.1096/fj.202000796rr
|View full text |Cite
|
Sign up to set email alerts
|

Single particle cryo‐EM of the complex between interphotoreceptor retinoid‐binding protein and a monoclonal antibody

Abstract: Interphotoreceptor retinoid‐binding protein (IRBP) is a highly expressed protein secreted by rod and cone photoreceptors that has major roles in photoreceptor homeostasis as well as retinoid and polyunsaturated fatty acid transport between the neural retina and retinal pigment epithelium. Despite two crystal structures reported on fragments of IRBP and decades of research, the overall structure of IRBP and function within the visual cycle remain unsolved. Here, we studied the structure of native bovine IRBP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The protein is synthesized by photoreceptors and is secreted into the interphotoreceptor matrix in a highly glycosylated form. IRBP binds all- trans and 11- cis -retinoids in addition to unsaturated fatty acids within its four homologous modules ( 25 , 26 , 27 ). Using Irbp -/- mice it was shown that this protein is not essential for visual cycle operation ( 28 , 29 ).…”
Section: Expression Of Visual Cycle Proteins In the Vertebrate Retinamentioning
confidence: 99%
See 1 more Smart Citation
“…The protein is synthesized by photoreceptors and is secreted into the interphotoreceptor matrix in a highly glycosylated form. IRBP binds all- trans and 11- cis -retinoids in addition to unsaturated fatty acids within its four homologous modules ( 25 , 26 , 27 ). Using Irbp -/- mice it was shown that this protein is not essential for visual cycle operation ( 28 , 29 ).…”
Section: Expression Of Visual Cycle Proteins In the Vertebrate Retinamentioning
confidence: 99%
“…Crystal structures of two modules were reported ( 32 , 33 ), revealing a conserved two-domain architecture consisting of an N-terminal ββα-spiral fold linked to a C-terminal αβα sandwich. The structure of full-length bovine IRBP was solved at a global resolution of 8.1 Å using cryoelectron microscopy ( 27 ), revealing a bent filament or “π”-shaped structure 14.1 nm in diameter, 39.1 nm in length, and 2.2 to 4 nm in width. This structure would enable IRBP to wrap around an unknown anchor to be retained in the extracellular space between the photoreceptors and RPE to prevent rapid clearance by the RPE.…”
Section: Expression Of Visual Cycle Proteins In the Vertebrate Retinamentioning
confidence: 99%
“…The different approaches used for mAb structural elucidation include spectroscopic methods [ 6 ], calorimetry [ 7 ], nuclear magnetic resonance [ 8 ], crystallography [ 9 ], electron microscopy [ 10 ], and mass spectrometry (MS)-based techniques [ 11 ]. Regardless of the technology used for structural characterizations, all of the methods face the inherent challenge of the homodimeric symmetry of antibodies.…”
Section: Introductionmentioning
confidence: 99%